Certificate of Origin Management in Supporting the Export Process: A Qualitative Descriptive Analysis on Marine Cargo Expeditions - Sumarwanto; Rustina, Evada; Dermawan, Arief; Nakuloadi, Hening; Aribowo, Fajar; Setiawan, Alam (Yayasan Ilomata, 2024)
The complexity of managing export documentation and the lack of knowledge of regulations in the importing country cause non-fulfilment of requirements and cancellation of exports. This study aims to determine the stages and the mechanism for managing certificates of origin in the export process by freight forwarding or marine cargo expedition representing the exporter. The research used qualitative descriptive methods and approaches. Data was collected by observation and documentation at two marine cargo expedition companies in Semarang, Central Java, Indonesia. Data is analyzed and presented using a flowchart diagram. The results show that these companies manage COO documents through the eSKA website, with the completeness of filling in the basic information of exporters, consignees, route and transport, and supporting documents, including export declaration, packing list, invoice, goods, and cost structure. Overall, export documents are indispensable for international trade as they ensure goods' legal compliance and smooth flow across borders. The role of the freight forwarding company or marine cargo expedition in this process is to advise the exporter on the required paperwork, ensure compliance with relevant regulations, and communicate with the appropriate authorities to obtain the certificate. The positive implications of this research are that the administration of export documentation, particularly Certificates of Origin (COO) via the eSKA platform by marine cargo expeditions, enhances time efficiency for exporters and proves efficacious in ensuring the legal compliance of COO document handling. Moreover, COOs can yield favourable effects through preferential tariffs, thereby augmenting the competitiveness of exported goods.